2015
DOI: 10.5489/cuaj.2899
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the direct impact of ketamine on urothelium using a tissue engineered bladder model

Abstract: Introduction: Ketamine is a common recreational drug. Severe lower urinary tract symptoms associated with its consumption have been reported, but little is known about the involved mechanisms. The effect of ketamine, which is excreted in urine, was evaluated by its application on an in vitro three-dimensional human tissue-engineered bladder model composed of an urothelium and a submucosa. Methods: Human urothelial cells were cultured with medium containing various concentrations of ketamine and harvested at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The use of these two cancer models for drug testing shows the potential to reduce the need for animal testing. The bladder mucosa model has also been used to study cystitis induced by ketamine use [ 292 ].…”
Section: Applications Of 3d Cell Culturesmentioning
confidence: 99%
“…The use of these two cancer models for drug testing shows the potential to reduce the need for animal testing. The bladder mucosa model has also been used to study cystitis induced by ketamine use [ 292 ].…”
Section: Applications Of 3d Cell Culturesmentioning
confidence: 99%
“…Ketamine on the other hand, was shown to be toxic to hepatocytes, urothelium, and neural cell [8][9][10]. Additionally, Du reported that clinically relevant concentration of ketamine induces osteoclast apoptosis and inhibits osteoclast formation from bone marrow cultures [11].…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al showed that ketamine‐induced toxicity to urothelial cells by high and sustained intracellular calcium ion concentration, which ultimately led to apoptosis 40 . This damage acts in a dose and time‐dependent manner, stimulating mitochondrial‐dependent and endoplasmic reticulum stress apoptosis and autophagy 41,43‐46 . Chuang et al showed that ketamine and norketamine levels were much higher in the 28‐day treated group compared to the 14‐day group.…”
Section: Evidencementioning
confidence: 99%